2023
DOI: 10.1002/adfm.202301815
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Property Enhancement in Orientation‐Modulated Perovskite La‐Doped SrTiO3 Thermoelectric Thin Films

Abstract: Thermoelectric oxide thin films are promising in chip cooling. The issues on the orientation of thin films are essential as they are related to the structures, morphologies, and thermoelectric properties. In this regard, the orientation modulation is conducted on La‐doped SrTiO3 thin films on (LaAlO3)0.3(Sr2TaAlO6)0.7 (LSAT) single crystal substrates. Layer‐by‐layer growth mode is found in (001)‐ and (110)‐ oriented thin films, resulting in few grain boundaries (GBs). In (111)‐oriented films, island growth mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 121 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…The observed shift of XRD peaks toward higher angles for V-SRCO could be attributed to lattice contraction caused by the generation of Vo. [31] Previous studies have shown that moderate doping is more favorable for the generation of Vo. [32,33] Moderate doping of Co atoms at the B-site in SRO, followed by etching with HCl solution, can result in the formation of Vo-rich V-SRCO.…”
Section: Resultsmentioning
confidence: 99%
“…The observed shift of XRD peaks toward higher angles for V-SRCO could be attributed to lattice contraction caused by the generation of Vo. [31] Previous studies have shown that moderate doping is more favorable for the generation of Vo. [32,33] Moderate doping of Co atoms at the B-site in SRO, followed by etching with HCl solution, can result in the formation of Vo-rich V-SRCO.…”
Section: Resultsmentioning
confidence: 99%
“…Thin film thermoelectrics (TFTE) has been an intriguing avenue of investigation in the recent past due to the plethora of technological applications such as self-powered wearable electronic devices, wireless sensor networks, microelectronics cooling, integrated circuits, etc. The potentiality of the TE thin films is evaluated via the dimensionless figure of merit , where S is the Seebeck coefficient, σ is electrical conductivity, κ is total thermal conductivity, and T is absolute temperature. Nevertheless, achieving a high figure of merit is a key challenge due to the interdependent relationship among the physical parameters S , κ, and σ. The simultaneous increase in Seebeck coefficient and the electrical conductivity, for a favorable enhancement of power factor (PF = S 2 σ), is tricky due to the inverse correlation of S and σ with carrier density n . Degenerately doped semiconductor thin films are the ideal choice for realizing a high TE power factor. …”
mentioning
confidence: 99%